Usability Testing of the National Digital Library of Theses and Dissertations Website Using Think Aloud and System Usability Scale (SUS) - Ketut Dian Suryasih; Putu Yudia Pratiwi; I Ketut Veda Suputra; I Komang Apriyatama Sukarma Putra (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2026)
The National Digital Library of Thesis and Dissertations is a website under the Taiwanese government that provides access to theses and dissertations from various universities in Taiwan. However, the current interface causes users to encounter difficulties in navigating and searching for information. This study aims to evaluate the website using think aloud method to identify problems experienced by users and System Usability Scale (SUS) to measure the level of usability. This study further aims to provide recommendations for improvement in the form of interface recommendation. Evaluation results show various obstacles, such as difficulty finding information, confusing navigation, and an unintuitive menu structure. The results show the Time-Based Efficiency (TBE) value obtained is 0.0129 goals/sec. The think aloud method found many usability problems on the website, ranging from navigation errors, action errors, and design errors. Meanwhile, the results of the System Usability Scale (SUS) analysis showed a score of 20. This means that the website falls into the poor category with an F grade. The results of the problem identification were then used as a reference in redesigning the website interface.